Strategy of Cuscus Conservation with Approach Wildlife Ecotourism - Henderina Lelloltery; M. M. S. Puttileihalat (Indonesian Cuscuses (Diprotodontia: Phalangeridae): Status and Perspective, 2022)
The cuscus animal is a protected animal, regulated in Government Regulation Number P.106, year 2018 concerning Protected Types of Plants and Animals. Although it is a protected species, hunting and catching of cuscus is still ongoing. Hunting results are generally sold for public consumption because it is one of the sources of animal protein favored by the community (Kunda, 2017a). The cuscus is a type of marsupial belonging to the Phalangeridae family and is described as a rather large and sturdy animal with a body length the size of a two-month-old pig. It was further explained that the sac in female animals is well developed, opens forward and has four nipples. Menzies (1991) described the cuscus as having a round head, having wool- like fur and being solitary, arboreal and nocturnal. Meanwhile, according to Flannery (1995a) cuscus (Phalangersp) is a large arboreal herbivore species (usually reaching a body weight of more than two kilograms) and utilizes leaves, fruit, flowers and tree bark as a source of food. Cuscus is one of five families belonging to the order Diprotodonta, namely the Phalangeridae family (Menzies, 1991). The distribution of the gray cuscus species (Phalanger) is very wide throughout the lowland rain forest of Papua up to an altitude of 1500 m above sea level. Meanwhile, the distribution of cuscus in Maluku includes Seram Island, Ambon Island, Buru, Banda, Saparua Island, Nusalaut, Haruku Island, Romang, Wetar, Tanimnar and Babar Island.